2014
DOI: 10.1183/09031936.00108514
|View full text |Cite
|
Sign up to set email alerts
|

Asthma, airflow limitation and mortality risk in the general population

Abstract: Asthma and chronic obstructive pulmonary disease co-exist in a significant proportion of patients. Whether asthma increases mortality risk among subjects with airflow limitation remains controversial. We used data from 2121 adult participants in the population-based TESAOD cohort. At enrollment (1972–73), participants completed questionnaires and lung function tests. Participants were categorized into four groups based on the combination of airflow limitation (AL: FEV1/FVC<70%) and physician-confirmed asthma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 34 publications
(36 reference statements)
5
32
1
Order By: Relevance
“…Many of the risk factors we identified for reduced growth of lung function have been reported previously, including maternal smoking during gestation, 29 reduced lung function at enrollment, 30 and increased airway hyperresponsiveness. 31 Among these factors, reduced lung function at baseline was the strongest predictor of longitudinal lung-function impairment.…”
Section: Discussionsupporting
confidence: 55%
“…Many of the risk factors we identified for reduced growth of lung function have been reported previously, including maternal smoking during gestation, 29 reduced lung function at enrollment, 30 and increased airway hyperresponsiveness. 31 Among these factors, reduced lung function at baseline was the strongest predictor of longitudinal lung-function impairment.…”
Section: Discussionsupporting
confidence: 55%
“…The presence of a linear trend across groups seems to confirm a linear relationship between FEV 1 /FVC reduction and mortality, as also shown by others [19] . The increased mortality in the F + /L -group, however, seems to be due to the confounding effect of age and sex.…”
Section: Discussionsupporting
confidence: 58%
“…Hence, the recent joint project of GINA and GOLD on the diagnosis of diseases of chronic airflow limitation describing the Asthma-COPD overlap syndrome (ACOS) emphasize that patients with obstructive airflow limitations who present features suggestive of asthma should be treated with inhaled corticosteroids (ICS) [12]. Furthermore, it has been repeatedly shown that airflow limitation in asthma is Lung function impairment increases with age 5 + MODEL associated with doubled risk of mortality, with respiratory failure as the most common cause of death [19,21]. An observational study based on the present cohort indicates that ICS treatment may reduce the annual loss of lung function by app.…”
Section: Discussionmentioning
confidence: 99%